Plan estratégico de marketing para la empresa Escacao - Bravo Moreira, Doriana Mabel (2022)
The present investigation is based on the elaboration of a Strategic Marketing Plan for the company Escacao, this company launched its product without carrying out a relevant market study, this so that they can know who each of their products is directed to. Now they´re bound to carry out a segmentation that allows them to approach a specific market or audience and meet their needs in a better way, for this reason this investigations objective is to determine the strategic dimensions of the Escacao company in the parish of La Calerita, situated in the province of Cotopaxi. A theoretical review was carried out that started with the history all the way to the technical scientific support that helped sustain the project; This research was carried out with a qualitative approach, which was supported by techniques such as observation and interviews applied to different populations according to the informational needs. The research started from the exploratory level that gave way to concept-analysis, and went on to the level of descriptive research which was used to define the characteristics of the targeted market and ended in the explanatory level where the causes of the problem were revealed to carry out an internal and external analysis which led to the design of marketing strategies that the company would use. Within the analysis and discussion of results, the fulfillment of the established specific objectives was carried out, which led to the development of the plan. As a first point, the corporate philosophy was set, this includes the mission, vision and corporate objectives of the company. The external analysis was carried out and a PESTEL analysis was proposed to reveal the environment of the company and to be able to identify the threats and opportunities of it. In this document the internal analysis of Escacao will be concluded including the market, the competition, the targeted audience, and the resources and capabilities of the company. The diagnosis allowed the creation of the SWOT and the product portfolio of Escacao. In the SWOT it is possible to see the internal and external factors of the company. In the product portfolio the BCG matrix was elaborated. Focusing on the strategical approach created by Porter strategies were generated, considering that the company is going to target a specific market niche which would allow to focus on the needs and priorities of the consumer. Likewise, the 4Ps were applied, these allow to determine each of the components that make up the Marketing Mix, which are the product, price, promotion and distribution of the company. Finally, action plans were made where the general objectives, strategies, goals and actions were set, assigning the responsibility holders for each of these strategies. A budget was finally proposed to find out how much it would cost the company to apply these strategies.